Development Strategy of Airborne Geophysical Exploration Technology - Shengqing Xiong; Jingwen Mao; Min Liu; Xihua Zhou; Xueyi Xu; Xuwen Qin; Liangquan Ge; Linfei Wang; Bin Chen; Tonglin Li; Yao Luo (中国工程科学)
Airborne geophysical exploration is an important and rapid method for mineral prospecting. China's airborne geophysical exploration technology has made great progress in the 21st century. However, existing technologies and equipment can hardly satisfy the new demand for key prospecting technologies and equipment for deep-Earth and deep-sea exploration in the new round of mineral prospecting breakthroughs in China. Focusing on the high-quality development of airborne geophysical exploration technologies in China, this study summarizes the development status of these technologies in China and abroad, evaluates the technological competition and development trends, and analyzes the major challenges faced by China in this field. Considering the new changes, characteristics, and trends of scientific and technological development, this study proposes a development roadmap of China's airborne geophysics exploration technologies, aiming at frontier technologies, such as superconducting sensors, full-tensor airborne-gravity gradient, full-tensor aeromagnetic gradient, multi-field-source full-depth airborne electromagnetism, and airborne seismic survey, as well as practical technologies urgently needed for the new round of mineral prospecting breakthroughs. Given the weaknesses in frontier research capability, technical adaptability, and innovation foundation, it is proposed to establish a national innovation center for airborne geophysical technologies, conduct the research and development of the fourth-generation airborne geophysical exploration technology, and build an integrated development system for airborne geophysical technical equipment.